PERBEDAAN KECEPATAN BERJALAN PADA PENGGUNA TRANSTIBIAL PROSTHESIS TIPE SACH FOOT DAN SINGLE AXIS FOOT: INDONESIA - Fatati, Muhibbah; Setyawan, Dwi; Fikria, Laila Hidayatul (Medical Journal of Nusantara, 2024)
Background: Below-knee amputations are the most common amputations in amputation patients. One of the mobility devices that can be used by amputation patients is a prosthesis. The main function of the prosthesis is to help its users be able to walk again and carry out activities normally . The appropriate type of prosthesis is a key factor in rehabilitation. The choice of foot prosthesis type is one of the factors that affect the gait parameter where in the gait parameter there is a walking speed factor. In most cases, the limb wearing the prosthesis does not compensate the amputated limb well, this can affect the speed of walking Method and Subject: This type of research uses analytical observational methods, with a cross-sectional research design. The subjects of this study were users of transtibial prosthesis type SACH foot and single-axis foot. The sample from this study was 16 respondents with purposive sampling techniques. The measuring instruments used in this study were meters and 10 MWT (Meter Walk Test). Results: Based on statistical tests using Mann Whitney, the results were found that there was a difference in walking speed in transtibial prosthesis users of SACH foot and single-axis foot types. Where the p-value (sig) < 0.05 is 0.001 with an effect size (large effect difference) of 0.83 which means it has a high or strong difference effect. Conclusion: there is a difference in walking speed in users of SACH foot and single-axis foot type prosthesis transtibials.